2016
DOI: 10.1111/jpn.12565
|View full text |Cite
|
Sign up to set email alerts
|

Response of lactating dairy cows to degree of steam‐flaked barley grain in low‐forage diets

Abstract: This study was conducted to investigate the effects of processing method (grinding vs. steam flaking) and increasing densities of steam-flaked barley grain on dry matter intake (DMI), rumen pH and fermentation characteristics, digestibility of dry matter in the total digestive tract (DDTT), and milk production of dairy cows. Eight multiparous mid-lactation Holstein cows averaging 103 ± 24 DIM, 44.5 ± 4.7 kg milk/day and weighing 611 ± 43 kg at the start of the experiment were used in a replicated 4 × 4 Latin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This observation is important because despite a similar forage level and particle size, physical characteristics of the diets changed due to nonforage dietary sources. In previous studies, using grain with different processing (Safaei et al., 2017) or different sources (Nasrollahi et al., 2012; Kargar et al., 2013; Kargar et al, 2015) changed effective fiber criteria like pef8 and pef1.18 and even peNDF8 and peNDF1.18. The intensity of the animal biological response (i.e., sorting or chewing) following a change of fibre effectiveness (i.e., pef or peNDF) needs to be further discussed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation is important because despite a similar forage level and particle size, physical characteristics of the diets changed due to nonforage dietary sources. In previous studies, using grain with different processing (Safaei et al., 2017) or different sources (Nasrollahi et al., 2012; Kargar et al., 2013; Kargar et al, 2015) changed effective fiber criteria like pef8 and pef1.18 and even peNDF8 and peNDF1.18. The intensity of the animal biological response (i.e., sorting or chewing) following a change of fibre effectiveness (i.e., pef or peNDF) needs to be further discussed.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is in contrast with our expectation, which was in accordance to previous trials reporting that an improvement of diet fermentability increases selection for long particles (Keunen et al, 2002; Maulfair & Heinrichs, 2013) or does not affect sorting (Kargar et al., 2013). Recently, (Safaei et al., 2017) demonstrated that with improving diet fermentability by decreasing density of flaked barley grain, sorting index of long particles was reduced. The sorting against long particles in the present study might be due to the physical characteristics of pellets used and the condition of ambient heat stress.…”
Section: Discussionmentioning
confidence: 99%
“…Lipids in extruded flaxseed are considered to be at least partially rumen-protected and thus can overtake the microbial bio-hydrogenation [ 39 , 40 ], while unprocessed oilseeds have a less influence on supplying n-3 on meat or milk [ 35 , 41 ]. Although various studies have been performed on the effect of different processing treatment (grounding vs. term-flaking) on cows performance and feed utilization [ 42 , 43 ], the lipid and FA metabolism of enriched n-3 sources subjected to different physical treatments has not yet been deepened. Regarding the amount of oilseed supplementation, in our FLAX diet, flaked flaxseeds was added at 2.13% of DM, thus in a lower concentration than the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our in situ experiment [52] showed that ground barley versus steam-laked barley increased organic mater disappearance (Figure 1) ), and efective degradability (60.6 versus 47.6%) of organic mater. In an in vivo study [53] using lactating dairy cows, we observed that the grinding versus steam-laking barley grain did not afect dry mater intake (23.6 kg/ day), digestibility of dry mater in the total digestive tract (71.0%), milk yield (43.4 kg/day), milk components, rumen pH, and molar proportions of acetate, propionate, and butyrate. The lack of diference between grinding and laking could be due to low grain inclusion rate and minimal diference in the particle size as barley was coarsely ground.…”
Section: Steam-laking Versus Rolling or Grindingmentioning
confidence: 99%